Evidence That Zika Virus Is Transmitted by Breastfeeding to Newborn A129 (Ifnar1 Knock-Out) Mice and Is Able to Infect and Cross a Tight Monolayer of Human Intestinal Epithelial Cells - Hubert, Mathieu; Jeannin, Patricia; Burlaud-Gaillard, Julien; Roingeard, Philippe; Gessain, Antoine; Ceccaldi, Pierre-Emmanuel; Vidy, Aurore (Frontiers in Microbiology, 2020)
Zika virus (ZIKV) belongs to the Flavivirus genus in the Flaviviridae family. Mainly transmitted via mosquito bites (Aedes aegypti, Aedes albopictus), ZIKV has been classified in the large category of arthropod-borne viruses, or arboviruses. However, during the past two outbreaks in French Polynesia (2013-14) and Latin America (2015-16), several cases of ZIKV human-to-human transmission were reported, either vertically via transplacental route but also horizontally after sexual intercourse. Interestingly, high viral burdens were detected in the colostrum and breast milk of infected women and mother-to-child transmission of ZIKV during breastfeeding was recently highlighted. In a previous study, we highlighted the implication of the mammary epithelium (blood-milk barrier) in ZIKV infectious particles excretion in breast milk. However, mechanisms of their further transmissibility to the newborn via oral route through contaminated breast milk remain unknown. In this study, we provide the first experimental proof-of-concept of the existence of the breastfeeding as a route for mother-to-child transmission of ZIKV and characterized the neonatal oral transmission in a well-established mouse model of ZIKV infection. From a mechanistical point-of-view, we demonstrated for the first time that ZIKV was able to infect and cross an in vitro model of tight human intestinal epithelium without altering its barrier integrity, permitting us to consider the gut as an entry site for ZIKV after oral exposure. By combining in vitro and in vivo experiments, this study strengthens the plausibility of mother-to-child transmission of ZIKV during breastfeeding and helps to better characterize underlying mechanisms, such as the crossing of the newborn intestinal epithelium by ZIKV. As a consequence, these data could serve as a basis for a reflection about the implementation of measures to prevent ZIKV transmission, while keeping in mind breastfeeding-associated benefits.